2022
DOI: 10.4102/hts.v78i3.6977
|View full text |Cite
|
Sign up to set email alerts
|

Environmental determinant of religious names: A study of Úgwú and naming among the Nsukka-Igbo people of Nigeria

Abstract: This article makes a contribution towards understanding the correlation between Úgwú (hill or mountain) and personal names among the Igbo people of Nigeria. Sacralisation of the natural environment which include hills or mountains is a belief that cuts across religions. Among the Igbo, the perceived sacred value placed on such natural environment prompted a series of socio-cultural changes. Personal names are usually drawn from deified entities such as the earth, sun, rivers, and so on. Studies on Igbo perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
(40 reference statements)
1
0
0
Order By: Relevance
“…Ngele et al (2017) have observed that 'for the Igbo, the sum total of their views about the world and life generally is very much shaped by their religion'. This is in line with the postulation of Agbo, Opata and Okwueze (2022) that in many African societies, the worldview of Nsukka people is anchored in religion. In other words, every human experience within a group is interpreted through religion.…”
Section: Introductionsupporting
confidence: 77%
“…Ngele et al (2017) have observed that 'for the Igbo, the sum total of their views about the world and life generally is very much shaped by their religion'. This is in line with the postulation of Agbo, Opata and Okwueze (2022) that in many African societies, the worldview of Nsukka people is anchored in religion. In other words, every human experience within a group is interpreted through religion.…”
Section: Introductionsupporting
confidence: 77%